Motivation and Training Impact toward Employee Performance at HR Bali Hotel - Yuni Devi Antari, Ida Ayu Nyoman; Diwyarthi, Ni Desak Made Santi; Jata, I Wayan (Journal of Hotel Management, 2025)
This research aims to determine the influence of motivation and job training on employee performance at HR Bali Hotel. The data analysis technique used is multiple regression analysis with the help of the Statistical Program for Social Science (SPSS). The research design employed is a quantitative design with a survey approach. The population used in this study involves all employees working at HR Bali Hotel, totaling 313 individuals. The sample used in this study is employees working at HR Bali Hotel, totaling 100 individuals. The sampling technique used is proportional random sampling using the Slovin formula. The results of the study show that motivation and job training, both partially and simultaneously, have a positive and significant effect on employee performance at HR Bali Hotel.